Organic fouling assessment of novel PES/SPSf/Double layered hydroxide mixed matrix membrane for water treatment application. (October 2020) - Ly, Quang Viet; Matindi, Christine N.; Kuvarega, Alex T.; Le, Quyet Van; Tran, Van Son; Hu, Yunxia; Li, Jianxin
Graphical abstract: Highlights: The DLH NMs were incorporated to prepare PES/SPSf mixed matrix membranes. The MMMs with 0.5 wt.% DLH NMs exhibited a low WCA, high water flux and elongation. The MMMs showed mitigated fouling potential from terrestrial-derived water sources. The MMMs posed more irreversible fouling regarding sodium alginate. The combination of ΔGho and U(h) is recommended to avoid any misinterpretation. Abstract: Fouling mitigation is of critical importance to warrant the widespread application of membrane filtration. Mixed matrix membranes (MMMs) have emerged as the attractive modified edition of traditional membrane due to their enhanced filtration performance, higher rejection and less fouling potential. This study examined the performance of MMMs by incorporating double layered hydroxide nanomaterials (DLH NMs) within the polyethersulfone/sulfonate polysulfone (PES/SPSf) blend matrix. The MMM with a loading rate of 0.5 wt.% DLH NMs showed an improved performance. The MMM exhibited enhanced antifouling ability than the pristine PES/SPSf membrane for terrestrial-derived organic matter. For sodium alginate (SA), the two membranes showed similar fouling potential, and the MMM even displayed worse irreversible fouling ascribed to higher roughness, reduced negative charge alongside the specific gel-box structure of SA-Ca 2+ . The fouling potential was further investigated by the thermodynamic analysis. The obtained results suggested that the specific free energies (ΔGho ) should be used with the free energies as a function of distance (U) to prevent any fouling misinterpretation. The work clearly implied that the organic fouling behavior during water treatment is somewhat complex and DLH NMs could be promising materials for MMMs to address terrestrial organic matter dominated water resources.